Analisa Laporan Keuangan Gudang Garam dan HM Sampoerna pada Masa Peralihan Covid-19 - Intri Ayu Murti; Sri Hermuningsih (Journal of Economics and Management Scienties, 2023)
This research was conducted to analyze how impacted the Indonesian cigarette industry was on the Covid-19 Pandemic phenomenon by analyzing the liquidity ratio (current ratio and quick ratio), activity ratio (receivables turnover ratio, inventory turnover ratio, fixed asset turnover ratio and total asset turnover ratio), and debt ratio by taking a sample of PT. Gudang Garam, Tbk and a comparison will be made with PT. HM Sampoerna, Tbk uses financial reports for the 2020-2021 financial year. The research method used is a qualitative descriptive method by collecting, processing, analyzing and presenting data descriptively with a sample of the financial statements of PT. Gudang Garam, Tbk and PT. HM. Sampoerna, Tbk for the 2020-2021 financial year. The research results obtained from comparing the financial performance of PT. Gudang Garam, Tbk with PT. HM. Sampoerna, namely the two companies are both liquid companies, able to pay off their short-term debt obligations, while for the activity ratio, PT. HM. Sampoerna has a pretty good score compared to PT. Gudang Garam, while for the debt ratio of PT. Gudang Garam, Tbk has a better ability to guarantee its debts than PT. HM. Sampoerna.